Comparing the Beginning- and End-of-Shift Attention Levels of Tehran's Pre-Hospital Emergency Staff with Those of Semnan - Abbasali Ebrahimian; Nader Khalesi; Maedeh Tourdeh; Hossein Dargahi (Tehran University of Medical Sciences, 2017)
Background and Aim: Emergency medical services (EMS) staff's attention level may be affected by various work conditions. This study aims to compare the beginning- and end-of-shift attention levels of Tehran's pre-hospital emergency staff with those of Semnan Province. Materials and Methods: This is a descriptive and cross-sectional research study conducted in 2013. In this study, 192 emergency medical technicians (EMT) of Tehran and Semnan Province participated. The research instrument was Bonnardel Attention Level Test. The participants' attention level was assessed at 10 am and 5 am. The data were analyzed by chi-square test and independent samples t-test.  Results: At 10 am (arrival attention), the average rate of attention level of Tehran's pre-hospital emergency staff was 0.49±0.25 and that of Semnan Province staff was 0.51±0.23. There was not a significant difference (p=0.58) at that time between the average rate of attention in these two groups. At 5 am (exit attention), however, the average attention level of Tehran's pre-hospital emergency staff was 0.45±0.25, and of Semnan Province staff was 0.55±0.20. At this time, there was a statistically significant difference (P= 0.044) between the average rate of attention in these two groups.  Conclusion: The means of arrival and exit attention levels in pre-hospital emergency staffs were moderate. Besides, there was no significant difference between the arrival attention levels of the two groups. Therefore, in order to increase the attention level in both groups, it is suggested that the workload and the length of shifts should be reduced for pre-hospital emergency staffs, specially in Tehran.